Mixotrophic fermentation for butanol production - Teixeira, Miguel Monteiro (2019)
The current economy is still dominated by the fossil-based chemical industry that represents a nefarious contribution to the environment. To avoid the permanence of this industry, the necessity to optimize fermentations to cost-competitive processes started to arise. It is known that heterotrophic organisms can transform organic carbon into fermentation products with great economic interest. However, for most fermentations where sugars are used as carbon source, over one-third of the sugar carbon is lost to CO2. The CO2 evolves from the Embden-Meyerhof-Parnas (EMP) glycolysis decarboxylation reaction that converts pyruvate into acetyl-CoA. To overcome this carbon loss, one route to recapture evolved CO2 using the Wood-Ljungdahl carbon fixation pathway (WLP), in a process called anaerobic, non-photosynthetic (ANP) mixotrophy, was reviewed in the present work. The ANP mixotrophy is defined as the concurrent utilization of organic (for example, sugars) and inorganic (for example, CO2) substrates in a single organism. Comparing with the EMP glycolysis, this metabolism allows higher productivities and lower CO2 emissions during fermentations. With the purpose of increasing the biobutanol productivity in anaerobic ABE fermentations performed by Clostridium beijerickii NCIMB 8052, a genetic engineering strategy was designed to enable the ANP mixotrophic metabolism in this strain. Through a set of different fermentations and bioinformatic researches, it was concluded that Clostridium beijerickii NCIMB 8052 is not naturally capable of performing the ANP mixotrophic metabolism due to a group of genes, considered as essential for the WLP, that were found to be missing in this strain. Several cloning techniques were used to insert and overexpress, via plasmid, these genes into Clostridium beijerickii NCIMB 8052. At the end, none of the genes were successfully transformed.